2003
DOI: 10.1111/j.1349-7006.2003.tb01511.x
|View full text |Cite
|
Sign up to set email alerts
|

The role of circulating IL‐8 and VEGF protein in the progression of gastric cancer

Abstract: Both vascular endothelial growth factor (VEGF) and interleukin 8 (IL-8) play an important role in the progression of gastric cancer (GC). In this study, we investigated whether circulating levels of VEGF or IL-8 in drainage veins of GC patients were correlated with any clinicopathological factors. Thirty-seven patients with primary GC who underwent gastrectomy at our department between 1999 and 2002 were analyzed. Blood samples were drawn from a peripheral vein just before surgery and from a drainage vein imme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
57
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(61 citation statements)
references
References 32 publications
(30 reference statements)
4
57
0
Order By: Relevance
“…In this study a significant correlation between augmented serum CXCL8 concentrations and an increasing tumor size was found, being consistent with previous studies (Konno et al, 2003;Ren et al, 2003;Ahmed et al, 2006). Locally, CXCL8 is known to moderate tumor growth and survival through neovascularization, as well as autocrine and paracrine mechanisms, but the exact mechanism for its raise in peripheral blood is unknown (Yuan et al, 2005;De Larco et al, 2004;Raman et al, 2007;Balkwill, 2003).…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…In this study a significant correlation between augmented serum CXCL8 concentrations and an increasing tumor size was found, being consistent with previous studies (Konno et al, 2003;Ren et al, 2003;Ahmed et al, 2006). Locally, CXCL8 is known to moderate tumor growth and survival through neovascularization, as well as autocrine and paracrine mechanisms, but the exact mechanism for its raise in peripheral blood is unknown (Yuan et al, 2005;De Larco et al, 2004;Raman et al, 2007;Balkwill, 2003).…”
Section: Discussionsupporting
confidence: 81%
“…Additionally, serum CXCL8 is susceptible to changes in its concentration due to dilution and its reliability to predict local changes should therefore be questioned. Although some studies showed a congruent increase in local and systemic CXCL8 values (De Andrés et al, 2013;Tamura et al, 2013) a study by Konno et al (2003) found a relationship between CXCL8 and a variety of tumor parameters in drainage veins of gastric cancer, whereas no significant relationship in peripheral veins (Konno et al, 2003). Moreover, the producing cells as well as the function of local and systemic CXCL8 may differ so that both should be included and compared in future studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, we speculate that treatment with VEGF antibody might prevent peritoneal recurrence of gastric cancer. Konno et al [23] reported that, in gastric cancer patients, VEGF levels in the peripheral veins were higher in patients with venous invasion. In our study, the mean number of tumor vessels patients with in type 3 or type 4 was significantly higher than that in patients with type 2, and the mean number of tumor vessels in those with high expression of VEGF tended to be greater than that in those with low VEGF expression.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, IL-8 is considered as a target for therapeutic intervention of cancers [26]. Increased serum levels of circulating IL-8 has been reported in GC patients than healthy controls [27,28], and IL-8 has been suggested to be associated with adhesion, migration, invasion and chemosensitivity, vascularity of GC [29][30][31]. In addition, previous studies have shown that several miRNAs, such as miR-520b, miR-106a, miR-106b, miR-23a, and miR-93 [32][33][34][35], are identified in diverse diseases by targeting IL-8 gene expression.…”
Section: Discussionmentioning
confidence: 99%